Development of a hookworm egg hatching assay to determine the ovicidal effects of anthelminthics - Erin Easland; Stefan Biendl; Jennifer Keiser (Parasites & Vectors, 2023)
Abstract Background Few anthelminthics are currently available, manifesting the urgent need for new treatment options. In vitro profiling of current anthelminthics against larval and adult stage helminths displayed varying effects on closely related worm species and between life stages of the same species. Conversely, limited research has been performed on the egg stage of human hookworms, and the effects of investigational compounds on the egg stage are not routinely assessed. Methods We profiled the development and hatching of Heligmosomoides polygyrus, Ancylostoma duodenale and Necator americanus eggs isolated from rodent faeces in liquid media with various nutrient levels, osmolar concentrations, and acidities in dependence on incubation temperature and light exposure. Incubation conditions were optimised to allow the study of drug effect on immature and embryonated eggs. We analysed concentration-effect relationships of commercially available anthelminthics over 72 h. Results Rapid embryonation and hatching were observed at room temperature with and without light exposure without nutrient supplementation in a wide range of acidities. Hookworms hatched optimally at room temperature in PBS achieving > 75% hatching over 34 h. Developmental delays were seen when eggs were stored at 4 °C with no effect on viability. Similar delays were also seen with increased osmolar concentrations resulting in decreased viability. Benzimidazole anthelminthics effectively reduced the viability and prevented hatching of hookworm eggs, with albendazole and thiabendazole eliciting particularly potent effects at EC50 values below 1 µM. Macrolide anthelminthics as well as emodepside, oxantel pamoate, and pyrantel pamoate were inactive while monepantel, levamisole, and tribendimidine displayed varied potencies among the hookworm species. Conclusion The presented egg-hatching assay will complement ongoing anthelminthic drug discovery and allow a full characterisation of drug activity against all life stages. In the development and application of the egg-hatching assay, good accordance was observed between the three hookworm species evaluated. Marketed anthelminthics show differences of drug action compared to larval and adult stages highlighting the importance of profiling drug activity against all life stages. Graphical Abstract